Crying-Laughing: The Case of Arthur in the Movie of Joker - Fania Diah Putri Rosyanti; Yuli Kuswardani; Lusia Kristiasih Dwi Purnomosasi (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
Arthur’s unresolved problems and many lies make Arthur a psychopathic figure. The purpose of this article is to describe how the main character turns his crying into laughing for expressing madness in Joker movie. The theory used by the researcher in this article is the psychoanalysis theory of Sigmund Freud (1856-1939). The method used is qualitative research with data collection techniques using documentation techniques, then the data is analyzed using 6 steps with Creswell's theory (2009). The result is found that the deeds performed by the main character in the Joker, Arthur Fleck, lead to a defense mechanism, namely Displacement. It reveals the form of causes in traumatic experience in his childhood physically and socially. The trauma lets him respond any triggers by laughing as he kills people, and the symptom shows the reaction of murdering is his own tortured experience imitation to others.